Repression of Gurken translation by a meiotic checkpoint in Drosophila oogenesis is suppressed by a reduction in the dose of eIF1A - Li, Wei (The Company of Biologists, 2014)
In Drosophila melanogaster, the anteroposterior (AP) and dorsoventral (DV) axes of the oocyte and future embryo are established through the localization and translational regulation of gurken (grk) mRNA. This process involves binding of specific factors to the RNA during transport and a dynamic remodeling of the grk-containing ribonucleoprotein (RNP) complexes once they have reached their destination within the oocyte. In ovaries of spindle-class females, an activated DNA damage checkpoint causes inefficient Grk translation and ventralization of the oocyte. In a screen for modifiers of the oocyte DV patterning defects, we identified a mutation in the eIF1A gene as a dominant suppressor. We show that reducing the function of eIF1A in spnB ovaries suppresses the ventralized eggshell phenotype by restoring Grk expression. This suppression is not the result of more efficient DNA damage repair or of disrupted checkpoint activation, but is coupled to an increase in the amount of grk mRNA associated with polysomes. In spnB ovaries, the activated meiotic checkpoint blocks Grk translation by disrupting the accumulation of grk mRNA in a translationally competent RNP complex that contains the translational activator Oo18 RNA-binding protein (Orb); this regulation involves the translational repressor Squid (Sqd). We further propose that reduction of eIF1A allows more efficient Grk translation possibly because of the presence of specific structural features in the grk 5′UTR.